PENGARUH PELAKSANAAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP PEMAHAMAN KONSEP PADA MURID SEKOLAH DASAR - Yusrianti Yusrianti (Universitas Negeri Makassar, 2016)
This research purpose to (1) identify the process of the Implamention of realistic mathematics education, (2) knowing the understanding concept in mathematics of students (3) search the influence of the implementation of realistic mathematics education against the understanding concept of students. This research is the experiment research, True Experiment Design by using pre-test post-test control group design involve one experiment class and one control class. To know about the result of this research, researcher used observation sheet and essay instrument which has 8 numbers. Result of observation data analyze show that the implamention of realistic mathematics education in first meeting got percentage 69,84% with enough categorized and increase in fourth meeting 96,82% with very good categorized. The result of understanding concept data analyze show that there is different result of understanding concept of student between the experiment class and the control class significantly. The average of experiment’s class score is 77,2, and the average of control’s class score is 66,9. So, the experiment’s class score is higher than the control’s class score. As conclusion that the implementation of realistic mathematics education has given positive effect to the understanding concept of student.